2016
DOI: 10.1007/s12011-016-0747-7
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Depletion of Cadmium in the Blood, Milk, Hair, Feces, and Urine of Cows During and After Treatment

Abstract: The objective of this study was to assess the accumulation and depletion of cadmium in the blood, milk, hair, feces, and urine of Holstein cows during and after treatment. Three Holstein cows received daily oral cadmium administrations (as cadmium chloride) of 0.182 mg/kg body weight/day for 21 days followed by a 63-day withdrawal period. Blood, milk, hair, feces, and urine were collected during treatment and withdrawal periods. Cadmium concentrations were measured by inductively coupled plasma mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…The concentration of Pb (0.028 mg L À1 ) in the urine of the sampled cows was lower than the range of 50-124 mg L À1 reported by Raghu (2015) in a study carried out with grazing cattle in India. In the case of Cd, the value detected in this work was higher than that reported by Su et al (2017), in an investigation where the accumulation and depletion of Cd in cows was evaluated. Cd values were higher in blood with respect to milk and urine, this could be since Cd has an efficient retention rate, with a half-life in the body of up to 30 years (Hu et al, 2012;Genchi et al, 2020).…”
Section: Urinecontrasting
confidence: 80%
See 2 more Smart Citations
“…The concentration of Pb (0.028 mg L À1 ) in the urine of the sampled cows was lower than the range of 50-124 mg L À1 reported by Raghu (2015) in a study carried out with grazing cattle in India. In the case of Cd, the value detected in this work was higher than that reported by Su et al (2017), in an investigation where the accumulation and depletion of Cd in cows was evaluated. Cd values were higher in blood with respect to milk and urine, this could be since Cd has an efficient retention rate, with a half-life in the body of up to 30 years (Hu et al, 2012;Genchi et al, 2020).…”
Section: Urinecontrasting
confidence: 80%
“…It also causes bone disorders such as osteoporosis and is known to inhibit the normal function of zinc and magnesium. On the other hand, when the excretion of Cd is high in urine, it means that there is severe damage to the kidneys and therefore, it is considered that urinary Cd reflects the body load of this element (Nordberg, 2009;Su et al, 2017). The concentration of As detected in urine 0.017 mg L À1 , is below that reported by Ghosh et al (2013) 0.122 mg L À1 .…”
Section: Urinementioning
confidence: 94%
See 1 more Smart Citation
“…Present content of Cd was higher than critical limit of Cd in blood of animals 0.5 mg/L as observed by WHO (2000). (Krupa et al, 2006: Cygan-Szczegielniak et al, 2014: Gabryszuk et al,2008:Su et al, 2017 (2010) noted values ranged from 0.02 to 0.08mg/L both of the ndings were Found lower than current observed concentration of Cd in irrigation water while safe limit of Cd in water was reported 0.01mg/L (Pescod ,1992) our concentration of Cd surpass this concentration. Alrawiq et al(2014) reported BCF values varied from 0.221-0.490 mg/kg lower than present study.…”
Section: Discussionmentioning
confidence: 54%
“…If the contact time increases, other side effects appear, including colic and anemia. The acute and rare side effect caused by oral absorption in children is encephalopathy (8)(9)(10). Cadmium is of metals that are widely dispersed in environment.…”
Section: Introductionmentioning
confidence: 99%